2019
DOI: 10.1016/j.jctb.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A proof of the Erdős–Sands–Sauer–Woodrow conjecture

Abstract: A very nice result of Bárány and Lehel asserts that every finite subset X or R d can be covered by f (d) X-boxes (i.e. each box has two antipodal points in X). As shown by Gyárfás and Pálvőlgyi this result would follow from the following conjecture : If a tournament admits a partition of its arc set into k quasi orders, then its domination number is bounded in terms of k. This question is in turn implied by the Erdős-Sands-Sauer-Woodrow conjecture : If the arcs of a tournament T are colored with k colors, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…That proof, however, only worked when C was a disk, and while the generalization to other convex bodies with a smooth boundary seemed feasible, we saw no way to extend it to arbitrary convex bodies. The proof of Theorem 1 relies on a surprising connection to two other famous results, the solution of the two dimensional case of the Illumination conjecture [22], and a recent solution of the Erdős-Sands-Sauer-Woodrow conjecture by Bousquet, Lochet and Thomassé [7]. In fact, we need a generalization of the latter result, which we prove with the addition of one more trick to their method; this can be of independent interest.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…That proof, however, only worked when C was a disk, and while the generalization to other convex bodies with a smooth boundary seemed feasible, we saw no way to extend it to arbitrary convex bodies. The proof of Theorem 1 relies on a surprising connection to two other famous results, the solution of the two dimensional case of the Illumination conjecture [22], and a recent solution of the Erdős-Sands-Sauer-Woodrow conjecture by Bousquet, Lochet and Thomassé [7]. In fact, we need a generalization of the latter result, which we prove with the addition of one more trick to their method; this can be of independent interest.…”
Section: Introductionmentioning
confidence: 89%
“…Theorem 9 (Bousquet, Lochet, Thomassé [7]). For every k, there exists an integer f (k) such that if D is a complete multidigraph whose arcs are the union of k quasi orders, then D has a dominating set of size at most f (k).…”
Section: Erdős-sands-sauer-woodrow Conjecturementioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 1 (Bousquet, Lochet and Thomassé [2]). Function f is well defined and f (n) = O(ln(n) · n n+2 ).…”
mentioning
confidence: 99%
“…Recently, Pálvőlgyi and Gyárfás [6] have shown that a positive answer to this problem would imply a new proof of a former result from Bárány and Lehel [1] stating that any set X of points in R d can be covered by f (d) X-boxes (each box is defined by two points in X). In 2017, Bousquet Lochet and Thomassé [2] gave a positive answer to the problem of Sands, Sauer and Woodrow.…”
mentioning
confidence: 99%